Strategi Peningkatan Kinerja Sekolah Melalui Bantuan Operasional Sekolah - Ginanjar Bachtiar Bachtiar; Rina Fitriana Fitriana; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Education is a key factor in the progress of a country. School Operational Assistance (BOS) is a government program to provide non-personnel costs for basic education units as implementers of the 12-year compulsory education program. the purpose of this study is to describe strategies for improving school performance through operational assistance based on fiscal policy. This study uses the literature review method to identify effective school performance improvement strategies through the use of School Operational Assistance (BOS). The research results show several effective strategies for improving school performance through BOS, including training and developing teachers, providing adequate learning resources, improving school infrastructure, and developing extracurricular programs. The implementation of these strategies needs to be supported by the involvement and active participation of all stakeholders, effective communication, transparency, accountability, and efficient management of available resources. Keywords: School Operational Assistance; Improvement strategy; School Performance; Education Quality; Fiscal policy